The left approach to social diversity: How the Communist Party interacted with Kerala’s social landscape? - Shahul Hameed Mattumannil (Cogent Social Sciences)
This article attempts to explain how the parliamentary left interacted with the social terrain of Kerala, which has a strong presence of organized social pressure groups. Kerala has a unique political landscape where radical left politics coexist with reactionary community forces. The early twentieth-century social reform movement has the credit of producing two parallel but antagonistic traditions that influenced modern Kerala politics more or less equally. The scholars have been polarised into two groups to explain what dominates Kerala politics, class, or caste. This work explicates these complexities by analyzing how the Communist Party engaged with the communities with the help of the literature on the democratic approach to social diversity. It tracks the evolution of the communist movement in Kerala in establishing and broadening its social base. It employs primary and secondary resources to examine the subject in question thoroughly. The primary resources used in the article are interviews with significant party leaders and ideologues. In doing so, this work argues that the Communist Party carefully balanced the ideological commitment to an integrationist approach to diversity on the one hand and a practical requirement for social accommodation and recognition on the other hand.